Very long-term outcome in resected and non-resected patients with temporal lobe epilepsy with medial temporal lobe sclerosis: A multiple case-study. (April 2019) - Grewe, P.; Schulz, R.; Woermann, F.G.; Brandt, C.; Doll, A.; Hoppe, M.; Tomka-Hoffmeister, M.; Bien, C.G.
Highlights: Very long-term outcome (i.e., ≥15 years follow-up) in TLE was assessed. Resected patients (RP) had a better seizure outcome than nonresected. RP had higher rates of memory complaints and lower verbal memory scores. Memory decline was seen after left-sided resections with good baseline performance. Long-term seizure freedom had the strongest impact on patients' subjective outcome. Abstract: Purpose: To investigate the very long-term (i.e., ≥15 years) seizure, cognitive and psycho-social outcomes in resected patients (RP) with TLE compared to control patients not having undergone epilepsy surgery. Methods: We applied a multiple case-study design including three non-resected patients (NRP) who were compared to a group of six RP. The latter were matched to the NRP according to clinical-demographic data. Outcome measures were various seizure, cognitive, and psycho-social variables. Results: Patients were 56–72 years old. Seizure and AED outcome was more favourable among RP. RP reported better self-perceived overall health but higher subjective memory complaints. Upon formal neuropsychological testing, RP presented with lower verbal memory scores. Very long-term memory decline was evident in left-sided RP with good baseline memory scores, while RP with lower baseline performance, right-sided RP and NRP remained stable. Seizure-freedom had remarkable effects on the relationship between objective and subjective outcome: seizure-free patients, in general, subjectively reported the best psychosocial and cognitive outcome – irrespective of neuropsychological test results. Conclusion: Our study suggests positive effects of TLE surgery in the very long-term course of ≥15 years postoperatively. Long-term seizure-freedom appears to have the strongest impact on patients' subjectively perceived psycho-social and cognitive outcome and may even outweigh actual memory disturbances and/or decline. Overall, our data do not support the assumption of a generally accelerated cognitive decline in patients with TLE.